2017
DOI: 10.1088/1748-605x/aa5522
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety and efficacy evaluation of ‘BioCaS’ bioactive calcium sulfate bone cement

Abstract: A new bioactive calcium sulfate-based formulation (named 'BioCaS') has been developed for bone filler applications. This is a self-setting injectable cement where the preset form comprises bassanite obtained from the uniform submicron-sized precursor crystals of gypsum, modified with hydrogen orthophosphate ions. The results of the safety and efficacy evaluation of BioCaS cement, done as per the International Standards and guidelines, are presented in this paper. The study plan consisted of in vitro screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As shown in Figure 5a, the cell viability of each concentration exceeded 100% on days 1, 3, and 5, suggesting a promoting effect on cell proliferation. Actually, numerous studies showed the cell proliferation ability of CSC was inferior to that of the control group, likely attributed to acidic byproducts generated during its degradation [29,[43][44][45][46][47]. It can be inferred that the biocompatibility of CS/MPP/C 3 S composite bone cement was greatly improved.…”
Section: Cytotoxicity and Osteogenic Differentiation In Vitromentioning
confidence: 99%
“…As shown in Figure 5a, the cell viability of each concentration exceeded 100% on days 1, 3, and 5, suggesting a promoting effect on cell proliferation. Actually, numerous studies showed the cell proliferation ability of CSC was inferior to that of the control group, likely attributed to acidic byproducts generated during its degradation [29,[43][44][45][46][47]. It can be inferred that the biocompatibility of CS/MPP/C 3 S composite bone cement was greatly improved.…”
Section: Cytotoxicity and Osteogenic Differentiation In Vitromentioning
confidence: 99%
“…As a BM that is widely used in clinical practice, calcium sulfate (CaSO 4 ) has various advantages, including good biocompatibility and degradability, sufficient sources, convenient sterilization, and other characteristics [ 217 ]. CaSO 4 cement has been approved by the US Food and Drug Administration (FDA) to be used in clinical bone defect treatment [ 218 , 219 ]. In the body, CaSO 4 can be completely degraded and absorbed through humoral-mediated dissolution and cell-mediated phagocytosis and does not have any significant impacts on Ca levels in blood [ 218 ].…”
Section: Srbmsmentioning
confidence: 99%
“…Animal tests have been formed to gain histological responses to the cements using the teeth of subject dogs, 56,109,[211][212][213][214][215][216][217][218] ferrets, 219 rats, 109,[220][221][222][223] monkeys, [224][225][226] and the bones of rats, 227,228 or rabbits. 85,[229][230][231][232] The advantage of animal testing is using multiple teeth and being able to microscopically examine the healing tissues. Notably, the overall trend in medical device development is to minimize animal testing and use more tissue-specific tests.…”
Section: Clinical Performance Of Calcium Silicate and Calcium Aluminate Cements In Dentistrymentioning
confidence: 99%